The Influence Of The Production Control System And Marketing Mix On Post Covid 19 Income Levels In UMKM Selling Wet Cakes In Kampung Melayu Village, Banyuwangi District - Helmi Agus Salim; Dewi Untari; Musaiyadi Musaiyadi (ABM: International Journal of Administration, Business and Management, 2023)
This study aims to determine the effect of the production control system and marketing mix on income levels during the pandemic at the UMK Sales of Wet Cake Products in Kampung Melayu Village, Banyuwangi District. In this study, researchers used primary data. Primary data in this study were obtained by distributing questionnaires. This study used 5 sellers of wet cake products as samples. The analytical techniques used include instrument testing, classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results showed that (1) the production control system partially significantly affected the level of income, (2) the marketing mix partially significantly affected the level of income, (3) and simultaneously the production control system and marketing mix had an effect on the level of income.